“Servirão lasanha no RU amanhã”: alguém fala assim? - Hora, Mariana Teixeira da (Universidade Federal de São Carlos, 2018)
In this research, we aim to analyse textbooks used as reference material in Portuguese as a foreign language (PFL) courses and its webpages, which are used as supplementary material. We intend to investigate grammar teaching of the future tense in Brazilian Portuguese on its two main forms: synthetic (amarei) and analytical (vou amar). Considering recent researches on the topic, we present the following questions: a) Is there correspondence in grammar description of the future tense in both textbooks and recent academic studies about the uses of this tense? b) Do the activities in textbooks and website provide elements that enable learners to express the future in different contexts, registers and categories of speech? Furthermore, we elaborated a prototype of a teaching unit that addresses the future tense, which was a result of the reflectance built along the research and aims to establish a connection between theory and practice. In effect, this analysis intends to promote reflection concerning grammar teaching in PFL, considering the real uses of both written and spoken language.
“Servirão lasanha no RU amanhã”: YDoes anyone talk like that?
Keywords: Português língua estrangeira; Ensino; Futuro; Livro didático; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA